1989
DOI: 10.1039/c39890001271
|View full text |Cite
|
Sign up to set email alerts
|

Direct biochemical nitration in the biosynthesis of dioxapyrrolomycin. A unique mechanism for the introduction of nitro groups in microbial products

Abstract: The nitro group of dioxapyrrolomycin (1) was shown to be introduced via direct biochemical nitration in cultures of the producing organism Streptomyces fumanus containing K'5N'803 as the sole source of nitrogen; the nitro group of dioxapyrrolomycin produced under these conditions contained the same ratio of 1 8 0 to 15N as was present in the labelled nitrate precursor, the extent of 1 8 0 enrichment of the nitro group being determined by negative electron impact mass spectrometry and 15N n.m.r. spectroscopy. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 3 publications
1
23
0
1
Order By: Relevance
“…Several biosynthetic pathways were proposed. One possibility is the direct nitration of aromatic compounds in the presence of KNO 3 in the medium [22] or by enzymatic oxidation of the amino groups [23]. Nitration can also be the result of peroxynitrite dependent or independent pathways [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Several biosynthetic pathways were proposed. One possibility is the direct nitration of aromatic compounds in the presence of KNO 3 in the medium [22] or by enzymatic oxidation of the amino groups [23]. Nitration can also be the result of peroxynitrite dependent or independent pathways [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…The source of the nitro functionality seems to be the inorganic nitrate present in the cultivation medium, as it has been previously described for Streptomyces fumanus, producing dioxapyrrolomycin (4). Recent studies of the biotransformation of tocopherols by Streptomyces catenulae revealed that the nitro derivatives, which were isolated from the culture medium, were formed by a combination of enzymatic nitrate reduction to nitrite followed by a nonenzymatic nitration (15).…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthetic nitration reactions are rare and usually involve the oxidation of an amine [33]. The chemical mechanism of a NOS-mediated nitration may be complex because NO is unlikely to react directly with indole.…”
Section: Biosynthetic Nitrationmentioning
confidence: 99%